Perancangan Interior Pusat Terapi Okupasi bagi Penderita Skizofrenia di Malang - Iwasil, Annelis; Sari, Sriti Mayang; Suryanata, Linggajaya (Intra, 2019)
Schizophrenia is a mental disorder that cannot completely be cured. However, some symptoms can be treated with cognitive behavioral treatment and therapy. Occupational therapy is a special treatment that aims to help people with physical, mental, or cognitive disabilities to be more independent in various aspects of life. The method that will be used for this design is a group therapy method so that it is specifically for schizophrenics who have socially recovered. Patients who are declared socially cured are patients who are able to interact with other people and other groups. The activities of group therapy that will be carried out in this treatment are dancing, making crafts, and painting. The concept used in this design is